2013
DOI: 10.1007/s00276-013-1108-2
|View full text |Cite
|
Sign up to set email alerts
|

The level of termination of the dural sac by MRI and its clinical relevance in caudal epidural block in adults

Abstract: Knowledge of the level of termination of the DS, the distance between the upper margin of the sacrococcygeal membrane and the DS, and the presence of Tarlov cysts on MRI images of before CEB is very important and might decrease the risk of dural puncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 17 publications
1
35
4
1
Order By: Relevance
“…The dural sac usually terminates between S1 and S2 vertebra, with the majority at S2 [8, 9, 15, 16]. In 1 to 5% of patients, the dural sac terminates at S3 or below [15, 16].…”
Section: Anatomymentioning
confidence: 99%
See 3 more Smart Citations
“…The dural sac usually terminates between S1 and S2 vertebra, with the majority at S2 [8, 9, 15, 16]. In 1 to 5% of patients, the dural sac terminates at S3 or below [15, 16].…”
Section: Anatomymentioning
confidence: 99%
“…In 1 to 5% of patients, the dural sac terminates at S3 or below [15, 16]. In addition, 1 to 5% of patients with low back pain or sciatica have a sacral Tarlov cyst [15–17], a perineural cyst that communicates with the dural sac and is filled with cerebrospinal fluid (CSF).…”
Section: Anatomymentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, most of the radiographic studies, instead, reported the DS termination. This anatomy was rather relevant to caudal epidural block than FT fusion site (Macdonald et al, ; Binokay et al, ; Senoglu et al, ). Their results were in concordance with cadaveric studies with most of the DS terminated at or below S1/S2 disk space.…”
Section: Discussionmentioning
confidence: 99%